Architectural prototyping: from CCS to .Net - F. Rodrigues, Nuno (2005)
Over the last decade, software architecture emerged as a critical issue in Software Engineering. This encompassed a shift from traditional programming towards software development based on the deployment and assembly of independent components. The specification of both the overall systems structure and the interaction patterns between their components became a major concern for the working developer. Although a number of formalisms to express behaviour and to supply the indispensable calculational power to reason about designs, are available, the task of deriving architectural designs on top of popular component platforms has remained largely informal. This paper introduces a systematic approach to derive, from CCS behavioural specifications the corresponding architectural skeletons in the Microsoft .Net framework, in the form of executable C and Cω code. The prototyping process is fully supported by a specific tool developed in Haskell